Penguatan Integritas Penyelia Halal Usaha Mikro dan Kecil (UMK) Bersertifikasi Halal di Kabupaten Semarang - Afifah, Hasna; Fittria, Anis (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The Halal Product Assurance Agency (BPJPH) launched several programs to increase halal certification in Indonesia. One of them is the Free Halal Certification (SEHATI) program. The SEHATI program is a free halal certification for Micro and Small Enterprises (MSEs) whose process is easy and simple. The halal certification process is assisted by Halal Production Process Assistance (P3H) which comes from the general public who have participated in the Training of Trainer (ToT). One of the important elements in SEHATI's halal certification is the existence of an internal auditor or called a halal supervisor in MSMEs. In Law Number 33 of 2014 Article 1 number 13 it is explained that a halal supervisor is an individual who has responsibility for the halal product process in a business. The difficulty of maintaining the integrity of halal supervisors in the halal production process is a problem in itself, this is because the internal auditor is appointed by the business owner himself, so it is possible that there are frauds that occur in the halal production process. This method of community service is Asset Based Community Development (ABCD). Strategies and activities carried out by service members are carried out, field assessments, Focus Group Discussion (FGD) and Training activities, and Internal Auditor Assistance activities. The changes in these service activities are, increasing the understanding of the integrity of internal auditors in Micro and Small Business Actors (MSEs), increasing the understanding of sharia insights and food safety for internal auditors in Micro and Small Business Actors (MSEs), and the formation of an internal auditor association (halal supervisors) in Semarang Regency.ABSTRAKBadan Penyelenggara Jaminan Produk Halal (BPJPH) meluncurkan beberapa program untuk peningkatan sertifikasi halal di Indonesia. Salah satunya program Sertifikasi Halal Gratis (SEHATI). Program SEHATI merupakan sertifikasi halal gratis untuk Usaha Mikro dan Kecil (UMK) yang prosesnya mudah dan sederhana. Proses sertifikasi halal dibantu oleh Pendampingan Proses Produksi Halal (P3H) yang berasal dari masyarakat umum yang telah mengikuti Training of Trainer (ToT). Salah satu elemen penting dalam sertifikasi halal SEHATI adalah adanya auditor internal atau disebut dengan penyelia halal dalam UMKM. Dalam UU Nomor 33 tahun 2014 Pasal 1 angka 13 dijelaskan bahwa penyelia halal merupakan individu yang memiliki tanggung jawab dalam proses produk halal di sebuah usaha. Sulitnya menjaga integritas penyelia halal dalam proses produksi halal menjadi permasalahan tersendiri, hal tersebut karena auditor internalnya diangkat oleh pemilik usaha sendiri, sehingga dimungkinkan ada kecurangan-kecurangan yang terjadi dalam proses produksi halal. Metode dalam pengabdian masyarakat ini adalah Asset Based Community Development (ABCD). Dilakukan strategi dan kegiatan yang dilakukan oleh pengabdi, assesment lapangan, kegiatan Focus Grup Discussion (FGD) dan Pelatihan, serta kegiatan Pendampingan Auditor Internal. Adapun perubahan kegiatan pengabdian ini adalah, meningkatnya pemahaman integritas auditor internal pada Pelaku Usaha Mikro dan Kecil (UMK), meningkatnya Pemahaman wawasan syariah dan keamanan makanan bagi auditor internal pada Pelaku Usaha Mikro dan Kecil (UMK), dan terbentuknya perkumpulan auditor internal (penyelia halal) di Kabupaten Semarang.